Validation of an Instrument to Measure the Variability of Fundamental Movement Choreography - Mikó, Alexandra; Karsai, István; Kovács, Katalin (Neveléstudomány | Oktatás – Kutatás – Innováció, 2024)
Creativity is a key and crucial competence in education. As several scientific publications have shown the positive effects of physical activity on creativity (Blanchette et al., 2005; Colzato et al., 2013; Santos et al., 2016 cited in Ruiz-Ariza et al., 2017), the role of physical education has been valorised in the field of creativity development (Sturza, 2014). Fundamental movement is essential to physical education lessons, providing teachers with a versatile tool to foster creativity. Different assessment procedures are crucial to measure the success of the learning process. We have not found an established and standardised protocol that objectively provides feedback on creative teaching-learning processes in PE lessons. Creative ideas can arise during the design of fundamental movement exercise sequences, and therefore, we have developed a set of criteria for evaluating the design of fundamental movement sequences. The study aims to present the criteria system and its validation.